Analyzing characteristics of collateral flow to parasylvian cortical arteries by three-dimensional digital subtraction angiography–magnetic resonance angiography fusion imaging in adult moyamoya disease - Jin Yu; Miao Hu; Jianjian Zhang; Jincao Chen (Frontiers in Neurology, 2023)
ObjectiveThe hemodynamic sources of recipient parasylvian cortical arteries (PSCAs) were significantly related to postoperative cerebral hyperperfusion (CHP) after bypass surgery in patients with moyamoya disease (MMD). The present study aimed to introduce a new method to investigate the characteristics of PSCAs hemodynamic sources and their relationships with clinical presentations in adult MMD and to provide preoperative evaluation for recipient vessel selection in MMD bypass surgery.MethodsThe hemodynamic sources of the PSCAs in 171 symptomatic MMD hemispheres were analyzed by three-dimensional digital subtraction angiography (3D-DSA) combined with magnetic resonance angiography (MRA) fusion imaging. The spatial and temporal characteristics of the hemodynamic sources of the PSCAs and their associations with the patient's demographics, Suzuki stage, and initial onset type were investigated.ResultsSix major types of hemodynamic sources in the PSCAs were observed. There was a significant difference between the hemodynamic sources of the PSCAs above and below the SF (P < 0.001). With advancing Suzuki stages, collateral flow to the PSCAs above the SF from the internal carotid arteries (ICAs) significantly decreased, while the non-ICAs increased (P < 0.001). Multivariate analysis revealed that hemodynamic sources of the PSCAs above the SF were significantly associated with patients' initial onset type (P = 0.026).ConclusionIn MMD hemispheres, the hemodynamic sources of the PSCAs above the SF are more varied than those below the SF and present a typical conversion trend from ICAs to non-ICAs with advancing Suzuki stages. Analyzing the hemodynamic sources of the PSCAs can help in understanding the conversion pattern of compensatory vascular systems, predicting episodes in MMD, and preoperatively evaluating suitable recipient vessel selection for bypass surgery to avoid postoperative CHP.